2021
DOI: 10.1002/jper.21-0144
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis outer membrane vesicles inhibit the invasion of Fusobacterium nucleatum into oral epithelial cells by downregulating FadA and FomA

Abstract: Background: Porphyromonas gingivalis (P. gingivalis) and Fusobacterium nucleatum (F. nucleatum) participate in the formation and progression of periodontitis. They can exert virulence by invading into host cells, but the interaction between them and their specific mechanisms remain unclear. The purpose of this study was to study the effect of P. gingivalis outer membrane vesicles (OMVs) on the ability of F. nucleatum to invade oral epithelial cells, and the reasons for the influence. Methods: The invasion abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 52 publications
2
17
0
Order By: Relevance
“…This ability was shown previously for several putative periodontal pathogens, including P. gingivalis, T. denticola, T. forsythia,a n dF. nucleatum (Inagaki et al, 2016;Lamont et al, 1995;Li et al, 2015;Zhang et al, 2021). Our data show that the invasion and survival capability of T.…”
Section: Discussionsupporting
confidence: 88%
“…This ability was shown previously for several putative periodontal pathogens, including P. gingivalis, T. denticola, T. forsythia,a n dF. nucleatum (Inagaki et al, 2016;Lamont et al, 1995;Li et al, 2015;Zhang et al, 2021). Our data show that the invasion and survival capability of T.…”
Section: Discussionsupporting
confidence: 88%
“…As a periodontal pathogen, F. nucleatum plays an indispensable role in the formation and growth of oral biofilms, affects the occurrence and development of periodontitis and is the main microorganism of biofilms in periodontal pockets ( Thurnheer et al, 2019 ; Curtis et al, 2020 ). Advances in research have revealed an increasing number of virulence factors ( Ellis and Kuehn, 2010 ; Zanzoni et al, 2017 ), and known virulence factors, new functions and mechanisms are continuously being reported ( Li D. H. et al, 2021 ; Zhang Z. et al, 2021 ). In addition to its significant “bridging” characteristics, the adhesin of F. nucleatum can bind to non-immune and immune cells, leading to gingival inflammation that subsequently develops into an irreversible periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from RadD, many other outer membrane proteins in F. nucleatum also have prominent roles in bacterial coaggregation and biofilm formation. The 42-kDa F. nucleatum major outer-membrane protein (FomA), which mediates coaggregation with P. gingivalis in periodontal pockets ( Kinder and Holt, 1993 ), has been reported to be a crucial factor for fusobacterial biofilm-bridge function ( Zhang et al, 2021 ). FomA cooperates with RadD and Fap2 to achieve binding between F. nucleatum and P. gingivalis ( Brennan and Garrett, 2019 ).…”
Section: The Role Of Fusobacterium Nucleatum In Pe...mentioning
confidence: 99%
“…However, the invasive feature of P. gingivalis to host cells is dramatically inferior to that of F. nucleatum ( Jang et al, 2017 ), which is in agreement with the finding of De Andrade et al (2021) that F. nucleatum is more virulent than P. gingivalis to host cells. It has been demonstrated that mixed infection with F. nucleatum strengthens the invasion capacity of P. gingivalis in oral epithelial cells ( Zhang et al, 2021 ). The “promoter” characteristic of F. nucleatum makes it a crucial pathogen in host mixed infection.…”
Section: The Role Of Fusobacterium Nucleatum In Pe...mentioning
confidence: 99%